Answer:
The answer would be 3.
Step-by-step explanation:
-2x= -6-x+3 First you would add the x to each side. Then you are left with..
-x= -6+3 Now add 3 to -6
-x= -3 Now to get rid of the negative sign on the x, divide each side by -1.
x=3 That would be your final answer.
To Check Your Work, plug in 3 to the two x in the original equation, and see if you will get a true statement.
-2x=-6-x+3
-2(3)= -6-3+3 The threes would cancel out because -3+3=0
-6 = -6 This is a true statement so that means x=3 is the correct answer